THE INFLUENCE OF UNIVERSITY BRAND IDENTIFICATION, POSITIVE ELECTRONIC WORD OF MOUTH (E-WOM) BEHAVIOR AND UNIVERSITY LIFE SATISFACTION ON STUDENTS' PSYCHOLOGICAL WELL-BEING - Abdul Ahmad Hafidh; Eka Septiarini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aimed to examine the relationship between University Brand Identification, Positive Electronic Word-of-Mouth (E-Wom) Behavior, and University Life Satisfaction and Students' Psychological Well-Being. This study use quantitative methodologies, namely statistical statistical systems, to assist in resolving previously identified research challenges. In this investigation, samples were collected from Cimahi City university students. University brand identification has a significant positive effect on positive E-wom behavior, University brand identification has a significant positive effect on student psychological well-being, and university life satisfaction has a significant positive effect on student psychological well-being.